Differences in structures of starch hydrolysates using saliva from different individuals. Issue 7 (7th February 2013) - Nantanga, Komeine K. M; Chan, Elizabeth; Suleman, Selina; Bertoft, Eric; Seetharaman, Koushik
Abstract: High salivary amylase activity is associated with improved glycemic homeostasis in humans. Therefore, high salivary amylase activity is associated with greater digestion of starch. However, it is unclear if the structures of the hydrolysates from different individuals with different salivary amylase activity are the same. To test this, cooked starch (1:2 starch/water ratio) was treated with saliva from six participants at equal activity and conditions mimicking oral digestion. Salivary amylase activities ranged from 470 × 10 3 to 118 × 10 3  U/mL among the participants. The composition of the hydrolysates was characterised by gel‐permeation chromatography. All samples gave rise to different and complex mixtures of hydrolysates with different breakdown structures. While saliva from participant 2 (high amylase activity) greatly reduced the high MW fraction, the saliva from participant 6 (low amylase activity) more extensively hydrolysed the starch to small MW fractions of oligosaccharides. These results show that different starch hydrolysates are produced during oral digestion by saliva from different individuals. Further research is therefore needed to understand if hydrolysate structure, rather than level of amylase activity, impacts glucose homeostasis.